Post-COVID myocarditis in adult patients (Research, Society and Development, 2022)
During the pandemic scenario, the investigation for information about COVID-19 becomes an increasing study in search of answers to the possible clinical repercussions of the disease, among them, myocarditis. Myocarditis is a pathology of diverse etiology that, as a result of infiltration in the myocardium, there is the release of aggressive mediators to the myocyte, causing necrosis and loss of myocardial structure. The present review aims to analyze the correlation between post-COVID adult patients and myocarditis, identify the profile of affected adult patients, as well as to describe their evolution and treatment. The study is a systematic literature review, performed from an article research from the period between 2020 and 2022 based on SciELO and PubMed databases. It was evidenced that associated comorbidities and advanced age of patients showed to be correlated factors with post-COVID myocarditis. However, because it is still a recent and controversial topic, it is perceived that the available data related to myocarditis in adult patients after COVID-19 infection need to be further investigated through new research to advance the understanding of post-COVID-19 myocarditis.